Model Perlindungan Anak Berbasis Asas The Best Interest of Child sebagai Kurir Narkotika - Randi Garandi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study examines legal protection for children acting as narcotics couriers in Indonesia, focusing on the application of the best interest of the child principle. Although Law No. 11/2012 on the Juvenile Criminal Justice System and Law No. 35/2014 on Child Protection prioritize diversion, rehabilitation and restorative justice over imprisonment, enforcement practice often applies prison sentences due to tension with the repressive provisions of Law No. 35/2009 on Narcotics. Children are frequently treated as perpetrators despite being exploited by adult networks. The proposed ideal protection model emphasizes preventive, protection-oriented repressive, rehabilitative approaches and cross-institutional collaboration to ensure optimal recovery and social reintegration of the child.